El contenido cultural en libros de texto de ELE destinados a estudiantes portugueses - Pérez Pérez, Noemí (Linguarum Arena, 2014)
The presence of the cultural content is fundamental in what concerns the learning of a foreign language; however, its inclusion tends to raise doubts the moment the teacher has to practice it on a daily basis. Within this framework, the textbook is a guide and a pedagogical tool which transmits, among other aspects, a certain image of the target culture. Therefore, this article aims to offer the results of a study having had into consideration the cultural contents of five works used in the Portuguese formal educational system in order to observe, precisely, the vision they provide of Spain, and its usage intends to supply a genuine assistance to the teacher when dealing with issues regarding the Spanish culture.